Hypoxic and hypercapnic ventilatory responses in rats with polycystic ovaries - Montrezor, Luis Henrique; de Carvalho, Débora [UNESP]; Dias, Mirela B. [UNESP]; Anselmo-Franci, Janete A.; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier B. V., 2015)
In female rats, a single injection of estradiol valerate (EV) results in effects that are similar to those observed in women with polycystic ovary syndrome (PCOS). We hypothesized that EV-induced PCOS affects breathing control based on evidence showing an influence of sex hormones on ventilation. To test this hypothesis, we studied the effects of EV treatment on the ventilation of female rats in air, in 7% CO2 and in 7% O2, at 30, 45 and 60 days after EV injection. The group examined 30 days after EV treatment showed a 61% reduction in the hypercapnic ventilatory response compared to the control group. Basal ventilation, hypoxic ventilatory response, and body temperature were not affected. These results, suggest that the hormonal changes observed in PCOS may result in a temporary inhibition of the central chemoreflex but do not influence basal ventilation or the hypoxic peripheral chemoreflex.
Keywords: Chemosensitivity; Hypercapnia; Hypoxia; Sex hormones; Ventilation